2020
DOI: 10.1093/rheumatology/keaa794
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps mediate joint hyperalgesia induced by immune inflammation

Abstract: Objective To evaluate the role of neutrophil extracellular traps (NETs) in the genesis of joint hyperalgesia using an experimental model of arthritis and transpose the findings to clinical investigation. Methods C57BL/6 mice were subjected to antigen-induced arthritis (AIA) and treated with Pulmozyme (PLZ) to degrade NETs or Cl-amidine to inhibit NET production. Oedema formation, the histopathological score and mechanical hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
1
27
0
2
Order By: Relevance
“…The literature describes that NETs can present direct cytotoxic effects on different mammalian cell types, including epithelial and endothelial cells, inducing apoptosis or necrosis (12, 46). Moreover, NETs could also activate different PRR receptors, such as toll-like receptor (TLR)-4 and 9, which mediate the release of inflammatory mediators; in turn, amplifying the direct effects of NETs (35). In this context, during COVID-19, apoptosis of lung epithelial was previously observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature describes that NETs can present direct cytotoxic effects on different mammalian cell types, including epithelial and endothelial cells, inducing apoptosis or necrosis (12, 46). Moreover, NETs could also activate different PRR receptors, such as toll-like receptor (TLR)-4 and 9, which mediate the release of inflammatory mediators; in turn, amplifying the direct effects of NETs (35). In this context, during COVID-19, apoptosis of lung epithelial was previously observed.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their microbicidal ability, NETs mediate lesions observed in several inflammatory diseases, including rheumatoid arthritis, lupus, diabetes, and sepsis (8,10,(35)(36)(37)(38)(39). In fact, inhibition of NETs production prevented lung, heart and liver lesions observed in experimental sepsis (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…This model is trigger primarily by immune processes and presents several characteristics of RA. Among others, a marked synovial-lining hyperplasia, proliferation of subliming cells, in ltration of in ammatory cells, local chemokine and cytokine production, pannus formation, (Schneider et al 2020). It is interesting to note that MG can also inhibit in ammatory pain and cell signaling induced by Toll-like receptor ligands (Correa et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the CCI model, IL-18 can feedback control its expression and regulate the other mediators involved in neuroinflammation, such as causing an up-regulation of MCP-1/CCL2, IL-4, or a down-regulation of IFN-γ ( 14 ). In patients with rheumatoid arthritis (RA), neutrophil extracellular traps (NETs) induced hyperalgesia by acting on Toll-like receptors (TLR-4 and TLR-9), and the production of NETs was positively correlated with the degree of pain ( 15 ). Other studies also reported that neutrophils infiltrated around the affected DRG release leukocyte elastase (LE) and played a role in the maintenance of chronic neuropathic pain in a diabetic neuropathic pain model.…”
Section: Immune Cell Participates In Peripheral Sensitizationmentioning
confidence: 99%